SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN JANTUNG PISANG GOROHO (Musa acuminafe L.) DENGAN METODE 1,1-DIPHENYL-2-PICRYLHIDRAZYL (DPPH) - Dr. Widysusanti abdulkadir S.Si.,M.Si.,Apt; Dr. Apt. Hamsidar Hasan S.Si.,M.Si; ading ading alamsyah (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Goroho banana (Musa acuminafe L.) has its own characteristics and is one of the local varieties of banana that is not widely known to people outside North Sulawesi. In addition, it is commonly used as an antioxidant. Antioxidants are substances that can improve the function of layers of blood vessels, inhibit blood platelet aggregation where it can stimulate the production of Nitric Oxide, which causes the relaxation of blood vessels and can reduce the sensitivity of Low-Density Lipoprotein (LDL) to the effects of free radicals. Therefore, this research aims to determine the chemical content and antioxidant activity of Goroho Banana (Musa acuminafe L.) by using DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Besides, the extraction of samples is carried out by employing extraction graded with n-hexane, chloroform, ethyl acetate, and ethanol solvents. Findings reveal that Goroho banana (Musa acuminafe L.) peel extract contains Alkaloid and Flavonoid compounds. Meanwhile, the value of antioxidant activity indicates that the IC50 value for n-hexane, chloroform, ethyl acetate, and ethanol extracts are 6.38, 5.48, 5.11, 4.19 ug/ml, respectively. In conclusion, the IC50 value discloses that the antioxidant activity is in a strong category.